Telescoping Intestine in an Adult - Khaldoon Shaheen; Naseem Eisa; Abdul Hamid Alraiyes; M. Chadi Alraies; Srinivas Merugu (Case Reports in Medicine)
Protrusion of a bowel segment into another (intussusception) produces severe abdominal pain and culminates in intestinal obstruction. In adults, intestinal obstruction due to intussusception is relatively rare phenomenon, as it accounts for minority of intestinal obstructions in this population demographic. Organic lesion is usually identifiable as the cause of adult intussusceptions, neoplasms account for the majority. Therefore, surgical resection without reduction is almost always necessary and is advocated as the best treatment of adult intussusception. Here, we describe a rare case of a 44-year-old male with a diffuse large B-cell lymphoma involving the terminal ileum, which had caused ileocolic intussusception and subsequently developed intestinal obstruction requiring surgical intervention. This case emphasizes the importance of recognizing intussusception as the initial presentation for bowel malignancy.